Preparation of a New Diphalant Based on Aminoguanidine, Soliguaidine and 2-Chloroethylphosphonic Acid - N. J. Shakarov; U. T. Usarov; I. Sh. Ergashev; M. N. Nomirov (American Journal of Biomedicine and Pharmacy, 2026)
The article discusses the development of technology for defoliants with insecticidal activity based on sodium chlorate, liquid magnesium chlorate, sodium tricarbamidochlorate, acephate, ethamipride, ethanol, and physical ethamipride with insecticidal activity. Based on the above, the purpose of this work is to develop and physico-chemical substantiation of the technology for obtaining defoliants based on salts of 2-chloroethylphosphonic acid, magnesium chlorate, guanidine and aminoguanidine.